Regarding the Montreal Protocol communication after the Kigali Amendment - Júlio J. Conde; Pablo Á. Meira-Cartea (Australian Journal of Environmental Education)
The Kigali Amendment introduced a new family of chemical compounds, which do not contribute to stratospheric ozone depletion but present a high global warming potential, under the watch of the Montreal Protocol in 2016. Earlier this year, a press note from the World Meteorological Organization entitled “Ozone layer recovery is on track, helping avoid global warming by 0.5°C” caught our attention because of the wrong conclusions that can be potentially drawn by laypersons due to an apparent linkage of ozone depletion and global warming problems. Public communication of the Montreal Protocol since the Kigali Amendment should be more careful than ever to avoid lessening the social perception of the threat of climate change, particularly considering that society already has a distorted representation of these problems, assuming causal relations between ozone depletion and climate change, that could lead to unfounded optimism towards the climate crisis.